Exports and new products in China - A generalized propensity score approach with firm-to-firm spillovers - Yundan Gong; Aoife Hanley (Kiel Centre for Globalization (KCG), 2021)
Underpinning China's technological advancement are the twin-engines of exports and innovation. To better understand China's meteoric economic transformation, we explore the extent to which new products are triggered by exports (direct effects) and by exposure to other exporters (indirect effects). Our methodology (generalized propensity score model) tackles two sources of selectivity bias - at the level of the firm and neighbourhood. Given that production is highly specialized and localized, it would be unusual if firms failed to learn from exposure to local exporters. Our findings reveal an overwhelmingly positive direct effect of exports on new product introductions. Also, a more modest spillover effect. Interestingly, firms with a reduced need to innovate (processing exporters) can also appropriate export spillovers. Our findings have implications for other developing countries seeking to maximise exporting in economic clusters, promoting innovation and ultimately growth.
Keywords: C38; D22; O12; O33; 330; export and innovation; export spillovers; Generalized Propensity Score